Analisis Kandungan Hidrokuinon dan Niasinamid pada Krim Pemutih Racikan di Klinik Kecantikan Wilayah Bekasi Selatan - Novia Ramadhani; Supandi; Estu Mahanani Dhilasari; Mabrurotul Mustafidah; Nelly Suryani; Marvel (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
Hydroquinone and niacinamide are whitening agents used alone or combined with cream products. Currently, the level of hydroquinone still exceeds the recommended safety limit. This study aimed to identify and determine the levels of hydroquinone and niacinamide in whitening creams prescribed by a beauty clinic in South Bekasi. The UV-Vis spectrophotometry was performed simultaneously. This study begins with the validation of analytical methods using validation parameters. Hydroquinone and niacinamide were identified using five samples, determined by purposive sampling, and measured at the maximum wavelengths of hydroquinone (293.4 nm) and niacinamide (261.4 nm). The results of the method validation showed that the linearity values expressed in the correlation coefficient (r) at concentrations of hydroquinone 8-28 µg/mL and niacinamide 10-34 µg/mL were 0,9999 and 0.998, LOD values 0,3990 and 0,3525 µg/mL, LOQ values were 1,3299 and 1,1749 µg/mL, RSD values of 0,0909% and 0,2591%, and recovery values were in the range of 99,154±0,223% to 107,387±0,121%. Based on the research data, it can be concluded that the five samples contained hydroquinone and niacinamide compounds at levels of 17,246% and 1,211% (A), 18,002% and 2,034% (B), 5,033% and 0,823% (C), 0,952% and 0,575% (D), and 0,10% and 5,367% (E). Samples A, B, and C have hydroquinone content exceeding the permitted maximum, while sample E contains niacinamide in an amount exceeding the recommendation.